2021
DOI: 10.1021/acs.energyfuels.1c00811
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Characterization and Reservoir Quality Evaluation of Analcite-Rich Shale Oil Reservoir from the Bohai Bay Basin

Abstract: Pore characteristics and shale oil reservoir quality strongly influences the petroleum occurrence, enrichment, and economic production. In this work, to characterize the pore system and evaluate the reservoir quality of analcite-rich shale oil reservoir, a total of 33 shale samples from the second member of the Paleogcene Kongdian Formation (Ek2) of Bohai Bay Basin were examined using a suite of techniques, including total organic carbon (TOC) content, X-ray diffraction (XRD), field emission SEM, gas (CO2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…X-ray diffraction (XRD) is an effective technique for quantifying the mineral composition of rock samples. The XRD experiments on powder E k 2 shale samples (<74 μm) were carried out using the SmartLab SE instrument produced by Rigaku, as described by Munson et al X-ray fluorescence (XRF) is a fast and nondestructive method for analyzing the spatial element distribution and stratification of samples. , The abundances of major elements, e.g., Al, Ca, Si, Fe, Mn, K, of bulk E k 2 samples (with an observed flat surface area of 2 cm × 2 cm) were measured by the micro-XRF M4 Tornado Plus manufactured by Bruker. Thin sections were prepared and observed in rectangular areas (2 cm × 2 cm) using a Leica DM750P optical microscope to further visualize the lamination characteristics of the shale samples.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…X-ray diffraction (XRD) is an effective technique for quantifying the mineral composition of rock samples. The XRD experiments on powder E k 2 shale samples (<74 μm) were carried out using the SmartLab SE instrument produced by Rigaku, as described by Munson et al X-ray fluorescence (XRF) is a fast and nondestructive method for analyzing the spatial element distribution and stratification of samples. , The abundances of major elements, e.g., Al, Ca, Si, Fe, Mn, K, of bulk E k 2 samples (with an observed flat surface area of 2 cm × 2 cm) were measured by the micro-XRF M4 Tornado Plus manufactured by Bruker. Thin sections were prepared and observed in rectangular areas (2 cm × 2 cm) using a Leica DM750P optical microscope to further visualize the lamination characteristics of the shale samples.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…The mineral composition of shale is complex, primarily composed of clay minerals (layered silicates), other common soil minerals (such as framework silicates like quartz and feldspar, as well as carbonates), and highly cemented aggregates of organic matter. The lithofacies of shale can be classified based on its mineral composition [14,15]. Studies have shown that shale of different lithofacies exhibits variations in mechanical properties [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Shale oil reservoirs are recognized for their tightness and pronounced heterogeneity, posing significant challenges for exploration and development efforts within the shale oil industry. The assessment of physical properties, critical for pinpointing productive layers and achieving efficient extraction, is closely linked to the reservoir’s rock components (RC) and pore structure (PS). Consequently, delving into the intricacies of RC and PS is essential for unlocking the potential of shale oil, a topic of growing scholarly interest. Technological advancements in high-resolution analytical methods, such as scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), and fluid injection techniques, have facilitated deeper insights into the micro- to nanoscale attributes of RC and PS in shale oil reservoirs. , These studies have revealed a diverse range of RC and a complex array of PS, underscored by their significant heterogeneity and the fundamental interplay among varying RC and PS. , Nonetheless, the exploration of these inter-relationships has largely been confined to qualitative analyses.…”
Section: Introductionmentioning
confidence: 99%